PENGARUH PENERAPAN METODE PEMECAHAN MASALAH TERHADAP KETERAMPILAN PENGAMBILAN KEPUTUSAN PADA MATA PELAJARAN IPA KELAS V SEKOLAH DASAR - Arie Widya Murni; Muchamad Nursalim; Sujarwanto Sujarwanto (Jurnal Visipena, 2022)
Research on the use of problem-solving methods conducted by researchers in fifth grade elementary school students aims to analyze the effect of applying problem-solving methods on decision-making skills in science subjects. Research method used in this study is a quantitative research method with a quasi-experimental type. The research design used is one group pre-test and post-test design. This research design takes three steps, namely starting from giving a preliminary test, giving treatment, and giving a final test. Data analysis used instrument testing, normality test, and t test. The results showed that the decision-making skills obtained an average pre-test value of 50.48 with a standard deviation of 9.09 while for the post-test the average value was 91.01 and a standard deviation of 3.63. The difference in the value of the pre-test and post-test of decision-making skills found the tcount value of 23.13 > ttable value of 2.04. So it can be concluded that the application of problem solving methods is very beneficial for students in the process of decision-making skills, especially in science subjects.